Callus Formation and Organogenesis of Potato (Solanum tuberosum L.) Cultivar Almera - G. Abd Elaleem2 and Rasheid S. Modawi2, Mutasim M. Khalafalla1*, Khadiga (Journal of Phytology, 2010)
A procedure for plant regeneration from callus culture of potato, Solanum tuberosum L. is described. Calli were induced from 1.0 cm2 tuber segment of potato cultivar Almera on Murashige and Skoog's medium (MS) supplemented with different levels (1.0-5.0 mg/l) of 2, 4-dichlorophenoxy acetic acid (2, 4-D). The highest degree of callus formation (3.0) and hundred percent (100%) of explants produced nodular calli on MS medium within 7-12 days when supplemented with 2.0-5.0 mg/l of 2, 4-D. Calli were differentiated into shoot-primordia when subcultured on MS medium supplemented with 1.5 -5.0 mg/l of thidiazuron (TDZ) and 2.0-5.0 mg/l of benzyladenine (BA). The best result for number of shoot per callus (3.3 ± 0.3) and longest shoot (0.8 ± 0.1) were obtained by using TDZ at 5.0 mg/l. Callus derived shoots were rooted most effectively in full-strength MS medium containing 1.0 mg L-1 IBA. The success of plant tissue culture for in vitro culture of potato was encouraged by acclimatization of the plantlets in the greenhouse conditions. Regenerated plants were morphologically uniform with normal leaf shape and growth pattern.